THE DYNAMICS OF STATE-SOCIETY RELATIONS AND DEMOCRATIZATION IN NIGERIA - OGBONNA Emmanuel Chijioke; ALUKO Bayode; ADEYANJU Joseph (International Studies Journal)
The paper focused on the understanding of state-society relations as a complex mix of interactions between the general citizens flanked by the masses and political leaders in determining the quality of governance in contemporary Nigeria. It draws from Easton's system theory as an analytical frame, underscoring the essence of democratisation as a continuum requiring the active input of critical citizens to impact on. It agrees that there is a rich culture of civil society in Nigeria, but appraises state-society relations as a larger umbrella with a greater incentive in public space construction. Focusing mainly on secondary data, the paper argues that all the factors facilitative of democratisation, free, fair, and periodic elections, protection of civil and political rights, political literacy, accountability, and freedom of the press, remain on the shoulders of constructive state-society relations. By implications, the democratic system at all time works as equilibrium constructed by the general citizenry, either as followers or in leadership positions – the citizens generally construct the type of governance they desire by either punishing fundamental transgression or rewarding good governance. This is against the backdrop of multiple academic validation about the failure of leadership in Nigeria's political development. Leadership failure, though germane, does not tell the entire story, as leadership is never subject to auto-correct, the course of leadership is usually stirred by critical citizenry. The paper concluded that Nigerian democratisation is troubled by the lopsided nature of state-society relations leading to the hijack of the state for private interest and impairment of democratic deepening. The work recommends the active role of critical citizens in effecting positive change to Nigeria's political development by driving the democratisation process. This is based on the understanding that democracies are never offered on a platter of gold; actively engaged citizens work towards the initiation, deepening and sustenance (consolidation) of democracy.